UJI KEPEKAAN BAKTERI YANG DIISOLASI DARI PASIEN DENGAN BAKTERIURIA TERHADAP ANTIBIOTIK AMOKSISILIN, LEVOFLOKSASIN DAN CIPROFLOKSASIN DI LABORATORIUM MIKROBIOLOGI RSUD RADEN MATTAHER JAMBI PERIODE OKTOBER - NOVEMBER 2016 (FAKULTAS KEDOKTERAN DAN ILMU KESEHATAN UNIVERSITAS JAMBI, 2017)
Abstract Urinary tract infection (UTI) one of infection resulting in significant morbidity and occasional mortality. Mostly, Community-acquired UTI caused by E. Coli. Antibacterial is the empiric treatment for UTI and the antibacterial resistance pattern of UTI can be changed by the place and time. Antibiotic is used to treat UTI such as cephalosporin, penicillin and quinolon. This research is to determine the antibacterial resistance pattern of amoxcillin, levofloxacin and ciprofloxcacin with disk diffusion method. The urine samples were taken from Laboratory of Microbiology Hospital Raden Mattaher Jamb with positive bacteriuria. This research obtained 46 samples. The most bacteries in urine were Staphylococcus haemolitycus (30,4%), E. Coli 13%, others (56,6%). Antibacterial susceptibility pattern for E. Coli showed that 66,6% sensitive to amoxcillin , 50% sensitive to ciprofloxacin and 83,3% sensitive to levofloxacin